Nutrient status of scavengable feed resources in crop and gizzard contents of three genotypes of ducklings - Rahman, MM; Khan, MJ; Akbar, MA (Bangladesh Journal of Animal Science, 2014)
An investigation was carried out with 54 scavenging ducklings of three genotypes belonging to three age groups (6, 10 and 14 weeks) taking from 3 areas reared under two feeding regimes. The birds were sacrificed from farmers house between 4.0 and 5.0 P.M. They were dissected to identify crop and gizzard contents (CGC). Cereal grains, bran, green forages, insects and worms were the main CGC and their composition varied significantly (p<0.01) with genotypes and feed. CGC were collected for chemical analysis. The CGC was processed and analyzed for proximate components, calcium (Ca) and total phosphorus (TP). It contained 88.06% DM, 10.15% CP, 13.65% CF, 2.89% EE, 15.51% Ash, 57.80% NFE, 1.42% Ca, 0.40% TP and 2264 kcal/kg DM TME. Genotypes and feed had significant effect (p<0.01) on CP, CF, EE, Ash, Ca and TP at 6 weeks of age but genotypes and feed showed no significant variations (p>0.05) on TME for the same period. It may be concluded that the scavenging feeds are deficient in CP, Ca and TP but excess in crude fibre. So, the concentration of the nutrients (except CF and ash) available to the scavenging ducklings under rural condition may be treated as below the suggested nutrient requirements for ducklings. DOI: http://dx.doi.org/10.3329/bjas.v43i3.21646 Bang. J. Anim. Sci. 2014. 43 (3): 185-191